2017
DOI: 10.1111/cod.12803
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of l‐carvone in toothpastes available on the Swedish market

Abstract: The majority of toothpastes on the Swedish market contain l-carvone, but the concentration hardly relates to the advertised flavour or labelled ingredients. It is hitherto unknown whether the found concentrations are sufficient for induction of contact allergy in individuals with healthy oral mucosa or in those with oral lichenoid lesions or other mucosal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…Sensitization to other flavours found in oral healthcare products, such as peppermint, cinnamal, cinnamyl alcohol and limonene, were not common in the investigated group, but a considerable number of patients had reactions to fragrance mix I and balsam of Peru, which contain flavour substances such as cinnamal and cinnamyl alcohol. Spearmint oil also contains 10-15% limonene (d-limonene) (1), a common fragrant constituent in cosmetic products (21) and also present in toothpastes (4). During a large part of the investigated time period the test preparation of limonene was not intentionally oxidized and it is essentially the oxidation products in limonene that are sensitizers, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitization to other flavours found in oral healthcare products, such as peppermint, cinnamal, cinnamyl alcohol and limonene, were not common in the investigated group, but a considerable number of patients had reactions to fragrance mix I and balsam of Peru, which contain flavour substances such as cinnamal and cinnamyl alcohol. Spearmint oil also contains 10-15% limonene (d-limonene) (1), a common fragrant constituent in cosmetic products (21) and also present in toothpastes (4). During a large part of the investigated time period the test preparation of limonene was not intentionally oxidized and it is essentially the oxidation products in limonene that are sensitizers, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Oral healthcare products are a major source of exposure, and carvone is a constituent of most toothpastes (4,5). Carvone is considered a weak sensitizer (6) and the prevalence of contact allergy in patch-tested cohorts has been estimated to be 1.6-2.8% (7,8).…”
mentioning
confidence: 99%
“…The results showed that L-carvone was found in 64 of 66 toothpastes with the concentration of 0.00005-0.35%. In ten toothpastes on which limonene was labelled, the concentration of L-carvone was higher than 0.1% [89]. One control study investigated whether contact allergies due to potential allergens were causing oral lichen lesions in patients exposed to a variety of dental material.…”
Section: Carvonementioning
confidence: 99%
“…If a weak (fragrance) contact allergen is found in many products, the patient may need to sort out many of his cosmetic products, as illustrated by a 60-year-old Spanish patient, who suffered from periorbital eczema due to sensitisation to benzyl salicylate, and identified 5 of her own products needing to be discarded [ 75 ]. L -Carvone is a known contact allergen and has been found (as constituent of mint flavour) in 64 of 66 Swedish brand toothpastes examined; in 10 of these the concentration exceeded 0.1% [ 76 ]. In case of contact allergy to such a widely used agent, formulation of a toothpaste by a pharmacy may be considered [ 77 ].…”
Section: Resultsmentioning
confidence: 99%